AN ANALYSIS OF THE STUDENTS’ DIFFICULTIES IN TOEFL READING SECTION AT THE FOURTH SEMESTER OF ENGLISH EDUCATION DEPARTMENT 2017 AT UIN ALAUDDIN MAKASSAR - riswanto, ahwandi riswanto (English Language Teaching for EFL Learners Journal, 2019)
This research aimed to analyze the students’ difficulties in TOEFL Reading Section at the Fourth Semester of English Education Department 2017.The population of this research was the fourth semester students of English Education Department 2017. The sampling technique used was total sampling. The objective of the research was to find out which skills difficulties existed on the TOEFL Reading Section. There were 2 instruments were used in this research namely test and questionnaire to analyze the students' difficulties in TOEFL Reading Section at the Fourth Semester of UIN Alauddin Makassar. The finding of this research showed that skill 3 75%, skill 6 84%, skill 7 81%, skill 8 77%, skill 11 79%, skill 12 81%, skill 13 86% were difficult to be answered by the students in the TOEFL Reading Section. While skills considered fair were skill 1 50%, skill 2 57 %, skill 4 68%, skill 5 50%, skill 9 68 % and skill 10 65%. While in the questionnaire indicated that the students responded “Agree” that skill 2 (48%), skill 3 (53%), skill 4 (45%), skill 5 (42%), skill 6 (37%), skill 7 (58%), skill 12 (50%), skill 13 (50%) were difficult skills. Base on the data found in the questionnaire that students responded “Disagree” skill 1 (51%), skill 8 (49%), skill 9 (52%), skill 10 (41%), skill 11 (42%) were not difficult skills based the data found in the questionnaire.